Analysis of load variations on kinetic energy and mechanical energy on an inclined plane - Moh Alfan; Wildan El Nahri; Muklis Maulana Sobri; Ulil Albab (Journal of Educational Engineering and Environment, 2025)
This study aims to determine the value of load variations on kinetic energy and mechanical energy. The method used in this study is the experimental method. The surface and length of the inclined plane are kept constant, with an adjustable angle of inclination. Determination of kinetic energy and mechanical energy is done by observing the slide of the object from the top of the inclined plane which is documented in video form. Based on the results of the study, it can be concluded that the mass of an object affects kinetic energy and potential energy. Based on the results of the trial, the greater the mass of the object, the greater the value of kinetic energy and potential energy. Kinetic energy is also related to the law of conservation of mechanical energy, which states that the total amount of kinetic energy and mechanical potential energy in a closed system remains constant, as long as there are only conservative forces acting on it.